SEJAUHMANA KEBEBASAN DALAM MEDIA SOSIAL: PERADABAN SOSIAL DAN PRIVASI DALAM SEMPADAN KEAGAMAAN - Ramli, Romlah (Journal of Techno-Social, 2016)
This paper explores the concept of civilization and religious boundaries to see the freedom of privacy in social media communication nowadays. Manners, human values and norms as referred by Malay Muslims had already outlined by religion. These guidelines have been seen for applications in communication trend as a results from the social media’s development. This relationship is discussed to see the social environment problems in society manners which result from the opennesss society and there is no control. It is from the the literature review and the discussions on the basic of Muslim’ etiquette social relationship and the freedom media’ usage as collective in communication. In gerenal, this paper has also formulated two manners include the normal social civilization which significant to be discussed in social network; social manners and ‘awrah’ etiquette. These dimensions can be applied directly to interpret social activities in social networks with respect to reference two major aspectscharacteristics of the social network.;visual and writing.